B.ED. COMPARATIVE STUDY OF ENVIRONMENTAL AWARENESS OF COLLEGE STUDENT: बी.एड. महाविद्यालय के विद्यार्थियों की पर्यावरणीय जागरूकता का तुलनात्मक अध्ययन - Srivastava, Sunita (International Journal of Research -GRANTHAALAYAH, 2015)
The study presented B.Ed. A comparative study was carried out on the environmental awareness of the college students. 40 students and 40 girl students were selected under the study. Environmental awareness of both the above groups was measured using survey method self-made questionnaire. The results obtained from the study make it clear that there is a significant difference in environmental awareness among art group and science group students. प्रस्तुत अध्ययन बी.एड. महाविद्यालयों के छात्र/छात्राओं की पर्यावरणीय जागरूकता पर तुलनात्मक अध्ययन किया गया । अध्ययन के अंतर्गत 40 छात्र एवं 40 छात्राओं का चयन किया गया । सर्वेक्षण विधि स्वनिर्मित प्रष्नावली का उपयोग करते हुए उपर्युक्त दोनों समूह का पर्यावरण जागरूकता का मापन किया गया । अध्ययन से प्राप्त परिणामों से स्पष्ट होता है कि कला समूह एवं विज्ञान समूह छात्रों में पर्यावरणीय जागरूकता में सार्थक अंतर पाया जाता है ।